Photocatalytic oxidation of fuel oxygenated additives in aqueous solutions - M. Krichevskaya; A. Kachina; T. Malygina; S. Preis; J. Kallas (International Journal of Photoenergy)
Experimental research of photocatalytical oxidation (PCO) of aqueous solutions of de-icing agents (ethylene glycol and ethylene glycol monoethyl ether) and methyl tert-butyl ether (MTBE) was undertaken. These chemicals are water-soluble components of jet and motor fuels accidentally disposed to the environment. Titanium dioxide (Degussa P25) under near-UV irradiation was selected as a photocatalyst. A slightly acidic medium was preferable for the process efficiency for MTBE, whereas a neutral medium was beneficial for de-icing agents and jet fuel aqueous extracts. TiO2 suspension fractional composition was found to be dependent on pH and the presence of organic admixtures: the minimum size of TiO2 particles at their maximum uniformity was established in an acidic medium, where the efficiency of PCO of de-icing agents was the poorest. On the other hand, neutral and slightly acidic media, beneficial for PCO efficiency, were favourable for particle agglomeration, which indicates a minimal role for photocatalyst particle size in PCO efficiency. PCO efficiency increased with increasing MTBE and icing inhibitor concentration. The biodegradability of aqueous solutions of oxygenated additives increased as PCO proceeded. The influence of mineral additives—sulphate, calcium, ferric and manganese ions—on the process efficiency was found to be complex. Special attention was paid to energy-saving PCO with a photocatalyst attached to buoyant glass micro-spheres and reduced intensity of stirring of the slurry.